1973
DOI: 10.1136/jnnp.36.4.574
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant drugs and spike propagation of motor nerves and skeletal muscle

Abstract: SUMMARY The propagation velocity of evoked muscle spikes was measured and normal values are presented. Carbamazepine, phenobarbitone, diazepam, and bromide-containing drugs were tested for their effect on conduction velocity of motor nerve and skeletal muscle fibres. All these drugs caused a decrease in spike propagation, both of motor nerves and skeletal muscle. After discussion of the probable mode and site of action of these drugs, it was supposed that the underlying eventsperhaps changes in permeability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 27 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Carbamazepine (used in the treatment of epilepsy, trigeminal neuralgia, and primary hemifacial spasm) has been used in MEM in doses up to 200 mg 3 times daily 23 . It reduces the excitability of nerve and muscle fibers 32,33 . This nonspecific effect might be the reason for success in MEM, although the exact mechanism is unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbamazepine (used in the treatment of epilepsy, trigeminal neuralgia, and primary hemifacial spasm) has been used in MEM in doses up to 200 mg 3 times daily 23 . It reduces the excitability of nerve and muscle fibers 32,33 . This nonspecific effect might be the reason for success in MEM, although the exact mechanism is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…23 It reduces the excitability of nerve and muscle fibers. 32,33 This nonspecific effect might be the reason for success in MEM, although the exact mechanism is unclear. Because of potential complications of bone marrow suppression and abnormal liver and kidney function, patients need monitoring by repeat full blood count, liver function, and electrolyte testing.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…One of the properties of carbamazepine is that it reduces the excitability of nerve and muscle fibres (Hopf, 1973;Schauff et al, 1974). This unspecific effect might also be the reason for success in these cases, although we do not know exactly the pathophysiology of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also found that the conduction velocity in the motoneuron (n. ulnaris) was slowed down, that the negativity of the action potential was increased, and that the force of contraction was reduced, especially after repetitive activation. The elbow flexor (biceps brachii) developed a greater voltage for a corresponding tension (0.4 mg' kg -I i.m., LUDIN and Du- BACH, 1971), but again the conduction velocity in the corresponding motor nerve or in the muscle was decreased (40 mg p.o., HOPF, 1973). The authors concluded that the most likely explanation for these effects was a direct effect on contractile elements or on the electromechanical coupling.…”
Section: Neuromuscular Transmission In Vivomentioning
confidence: 99%